Hubungan Antara Pengetahuan Dan Sikap Pelajar Terhadap Penyalahgunaan Narkotika, Psikotropika, Dan Zat Adiktif Tahun 2019 - Andzar Fikranus Shofa; Chartyka Situmeang; Widayanti (Journal Prima Health Science, 2020)
The high number of drug users and drug abuse in West Java amongstudents is the reason for this research. The purpose of this study wasto determine whether there is a relationship between knowledge andstudent attitudes at SMAN 1 Tambun Utara Bekasi against drug abusewith characteristics seen from age, sex, having a dealer or user, andresidence status. The method used in this research is to usequantitative descriptive methods with a research design using Chisquare,with a total sample of 100 students, consisting of classes X,XI, and XII. From the results of this study obtained knowledge, aperson's attitude, age, gender, whether living with parents or not,have a user's friend or not and have a dealer or not, these factors donot affect the occurrence of abuse, from the results obtained by thelevel of student knowledge that good about drugs is still low with avalue of 11% of the total respondents and as much for lack ofknowledge or still high enough in the percentage of 89%, but theattitudes of students of SMAN 1 Tambun Utara not to use drugs asmuch as 99% have a positive attitude. Although the knowledgepossessed is still lacking, a positive attitude still dominates not tocommit acts of abuse, and from the test results, it is found that there isno relationship between variables, which can be said that abuseoccurs not because of knowledge or one's attitude.